Life and death of a sewage treatment plant recorded in a coral skeleton δ15N record. Issue 1 (15th July 2017) - Duprey, Nicolas N.; Wang, Xingchen T.; Thompson, Philip D.; Pleadwell, Jeffrey E.; Raymundo, Laurie J.; Kim, Kiho; Sigman, Daniel M.; Baker, David M.
Abstract: We investigated the potential of coral skeleton δ 15 N (CS-δ 15 N) records for tracking anthropogenic-N sources in coral reef ecosystems. We produced a 56 yr-long CS-δ 15 N record (1958–2014) from a reef flat in Guam that has been exposed to varying 1) levels of sewage treatment 2) population density, and 3) land use. Increasing population density (from < 30 to 300 ind·km − 2 ) and land use changes in the watershed resulted in a 1‰ enrichment of the CS-δ 15 N record until a sewage treatment plant (STP) started operation in 1975. Then, CS-δ 15 N stabilized, despite continued population density and land use changes. Based on population and other considerations, a continued increase in the sewage footprint might have been expected over this time. The stability of CS-δ 15 N, either contradicts this expectation, or indicates that the impacts on the outer reef at the coring site were buffered by the mixing of reef water with the open ocean. Highlights: CS-δ 15 N records responds to human population density change for > 30 ind·km − 2 . Sewage treatment systems may decouple population changes and CS-δ 15 N variation. CS-δ 15 N records can bring information the history of coastal water quality. It is crucial to obtain baseline δ 15 N values from periods of no human influence.